Pemanfaatan Ekstrak Kulit Akar Mengkudu Sebagai Bahan Pewarna Alami Benang pada Kain Tenun Ikat - Fathurrahmaniah, Fathurrahmaniah; Pranamantara, Efraim Jehane (STKIP HARAPAN BIMA, 2025)
This research was conducted to respond to the need for the use of natural dyes that are more environmentally friendly and safer for health than synthetic dyes. One alternative is the use of natural dyes by utilizing the bark of the noni root (Morinda citrifolia Linn). The purpose of this research is to produce natural dyes from the bark extract of the noni root for use on ikat weaving yarn. The method used is a case study with the technique of thread washing stage, extraction and dyeing stage, color fixation stage, drying, observation of results, then the data is analyzed descriptively narrative. The results of the study show that extraction is carried out by the process of removing impurities in the yarn, dyeing fixation and drying. This natural dye extract is produced from boiling the bark of the noni root for 60 minutes and the dyeing is done traditionally and fixation is done using lime and tunjung as much as 1% which respectively produces a pink color on the lime and a reddish brown color on the tunjung. The use of the bark root of the noni can be used as an alternative natural dye for yarn used as the basic material for making ikat woven fabrics.